Empire and Identity in Guizhou Local Resistance to Qing Expansion - Weinstein, Jodi L.; Project Muse. (2014)
"Empire and Identity in Guizhou is a study of stormy ethnic relations in eighteenth-century Guizhou Province between the Qing state and the Zhongjia ethnic group, which culminated in the Nanlong Uprising in 1797. As the imperial state extended its control into frontier areas such as Mongolia, Tibet, and the southwest, it encountered difficulty incorporating non-Han people into the empire. The Zhongjia in particular were difficult to control, because the state could not employ religion as a political tool, as it did with ethnic minorities who were Buddhist; nor were literary tactics useful with the nonliterate Zhongjia. Weinstein shows how the Zhongjia maintained autonomy through livelihood choices, and how their "creative resistance" ranged from subterfuge to outright rebellion. This engagingly written and dramatic case study demonstrates how the Qing empire really worked and contributes toward a broader understanding of imperialism and colonialism"--
"This historical investigation describes the Qing imperial authorities' attempts to consolidate control over the Zhongjia, a non-Han population, in eighteenth-century Guizhou, a poor, remote, and environmentally harsh province in Southwest China. Far from submitting peaceably to the state's quest for hegemony, the locals clung steadfastly to livelihood choices--chiefly illegal activities such as robbery, raiding, and banditry--that had played an integral role in their cultural and economic survival. Using archival materials, indigenous folk narratives, and ethnographic research, Jodi L. Weinstein shows how these seemingly subordinate populations challenged state power.Jodi L. Weinstein teaches history at The College of New Jersey"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: SOCIAL SCIENCE / Anthropology / Cultural; HISTORY / Modern / 19th Century; HISTORY / Asia / China; Bouyei (Chinese people) -- China -- Guizhou Sheng -- History -- 18th century; Guizhou Sheng (China) -- Ethnic relations -- History -- 18th century; Electronic books